1997
DOI: 10.1002/(sici)1099-1395(199706)10:6<445::aid-poc904>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

An Electronegativity Model for Polar Ground-State Effects on Bond Dissociation Energies

Abstract: Homolytic bond dissociation energies are a composite of the radical stabilization energies (RSE) of the product radicals and the polar ground-state stabilization energies (PSE) of the reactant molecules. Substituent effects on the PSE are rationalized in terms of changes in the difference of group electronegativities. Thus, the PSE is composed of a bond polarity term, which measures the contribution due to the change in the electronegativity difference between the atoms in the bond, which is broken, and a pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 98 publications
6
28
0
Order By: Relevance
“…26 This polar effect was attributed to a ground-state stabilization, 26 which arises from the action of the substituents on the strength of the polar bond. 27,28 A similar polar effect is expected for the decarbonylation, but the data set is too small and displays insufficient variation to separate a potential polar effect from the larger radical effect. In fact, a two-parameter Hammett treatment 26 revealed that the inclusion of a polar contribution (s pol ) does not improve the correlation between logk X CO ak H CO and s rad significantly.…”
Section: Substituent Effectsmentioning
confidence: 62%
“…26 This polar effect was attributed to a ground-state stabilization, 26 which arises from the action of the substituents on the strength of the polar bond. 27,28 A similar polar effect is expected for the decarbonylation, but the data set is too small and displays insufficient variation to separate a potential polar effect from the larger radical effect. In fact, a two-parameter Hammett treatment 26 revealed that the inclusion of a polar contribution (s pol ) does not improve the correlation between logk X CO ak H CO and s rad significantly.…”
Section: Substituent Effectsmentioning
confidence: 62%
“…A strong correlation of the BDE with the substituent constant σ + has been previously established (44, 46), which was therefore also employed in the present analysis in order to provide a thermodynamic foundation for the investigated kinetic substituent effects. The detailed underlying reasons for the better correlation with σ + and the observed negative ρ value are in debate (44, 47–50), but it appears appropriate to argue that the removal of a hydrogen atom from the oxygen results in a net loss of electron density on the oxygen, which is better accommodated by electron‐donating substituents (negative ρ value).…”
Section: Resultsmentioning
confidence: 99%
“…The difference of the C−C bond energy in Ph−CH 3 as compared to that in CH 3 −CH 3 is 11.8 kcal/mol. In terms of radical stabilization energy, , the difference between half of the BDEs of a symmetrical and nonpolar C−C bond in Ph−Ph and the one in CH 3 −CH 3 is 12.3 kcal/mol, i.e., the difference in stability of the methyl versus phenyl radicals. Thus, the 11 kcal/mol higher C−C bond energy of PhC(O)O• as compared to that of the CH 3 C(O)O• radical is mainly attributable to the difference in the stability of the methyl vs phenyl radicals.…”
Section: Discussionmentioning
confidence: 99%